1968
DOI: 10.1002/ijc.2910030610
|View full text |Cite
|
Sign up to set email alerts
|

Lymph‐node metastases after intratibial transplantation of tumors

Abstract: Ehrlich carcinoma and Sarcoma (Pearce and Brown, 1923;Black, 1964) and a few mouse tumors such as the Lewis lung sarcoma (Schatten, 1958; Ketcham et al., 1966).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1974
1974
1983
1983

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Other examples are intratibial (15) and intratesticular (55) implantation. Whereas the latter rarely show parenchymatous secondaries, implantation in the footpad often produces a tumor which metastasizes early and with high frequency to the lungs.…”
Section: Implantation Sites That Promote Lymphatic Disseminationmentioning
confidence: 99%
“…Other examples are intratibial (15) and intratesticular (55) implantation. Whereas the latter rarely show parenchymatous secondaries, implantation in the footpad often produces a tumor which metastasizes early and with high frequency to the lungs.…”
Section: Implantation Sites That Promote Lymphatic Disseminationmentioning
confidence: 99%
“…In the few animal tumor systems in which lymphatic metastasis has been studied in any detail (Table 6), tumor cells are injected into tissues with a well-developed lymphatic drainage. The footpad is used most commonly for this purpose, but lymphatic metastasis has also been reported following injection of tumor cells into the tail (165), testis (166), and bone marrow (167). In other studies tumor cells have been injected directly into lymphatic channels (168,169).…”
Section: Models Of Lymphatic Metastasismentioning
confidence: 99%
“…This obstruction is somewhat reduced by irradiation of the node or cortisone treatment (Kallum and Saldeen, 1967;Stoker, 1969a and b). Fisher and Fisher (1 967b) however demonstrated rapid recovery of tumour cells from the efferent vessel of a lymph node after cannulation of the afferent vessel and introduction of tumour cells into it, and Franchi et al (1968) demonstrated consistent lymph node metastasis after intratibial implantation of two mouse tumours. Many of these experiments did not involve true metastasis in that tumour cells were injected into cannulated lymphatics.…”
mentioning
confidence: 96%